Carotid Artery Stiffness Mechanisms Associated With Cardiovascular Disease Events and Incident Hypertension: the Multi-Ethnic Study of Atherosclerosis (MESA). Issue 3 (13th January 2022) - Pewowaruk, Ryan J.; Korcarz, Claudia; Tedla, Yacob; Burke, Gregory; Greenland, Philip; Wu, Colin; Gepner, Adam D.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Elastic arteries stiffen via 2 main mechanisms: (1) load-dependent stiffening from higher blood pressure and (2) structural stiffening due to changes in the vessel wall. It is unknown how these different mechanisms contribute to incident cardiovascular disease (CVD) events. Methods: The MESA (Multi-Ethnic Study of Atherosclerosis) is a longitudinal study of 6814 men and women without CVD at enrollment, from 6 communities in the United States. MESA participants with B-mode carotid ultrasound and brachial blood pressure at baseline Exam in (2000–2002) and CVD surveillance (mean follow-up 14.3 years through 2018) were included (n=5873). Peterson's elastic modulus was calculated to represent total arterial stiffness. Structural stiffness was calculated by adjusting Peterson's elastic modulus to a standard blood pressure of 120/80 mm Hg with participant-specific models. Load-dependent stiffness was the difference between total and structural stiffness. Results: In Cox models adjusted for traditional risk factors, load-dependent stiffness was significantly associated with higher incidence of CVD events (hazard ratio/100 mm Hg, 1.21 [95% CI, 1.09–1.34] P <0.001) events while higher structural stiffness was not (hazard ratio, 1.03 [95% CI, 0.99–1.07] P =0.10). Analysis of participants who were normotensive (blood pressure <130/80, no antihypertensives) at baseline exam (n=2122) found higher load-dependent stiffness was also associated with significantly higher incidence of hypertension (hazard ratio, 1.53 [95% CI, 1.35–1.75] P <0.001) while higher structural stiffness was not (hazard ratio, 1.03 [95% CI, 0.99–1.07] P =0.16). Conclusions: These results provide valuable new insights into mechanisms underlying the association between arterial stiffness and CVD. Load-dependent stiffness was significantly associated with CVD events but structural stiffness was not.